2007
DOI: 10.1128/jvi.01568-07
|View full text |Cite
|
Sign up to set email alerts
|

Primary Human Splenic Macrophages, but Not T or B Cells, Are the Principal Target Cells for Dengue Virus Infection In Vitro

Abstract: Understanding the pathogenesis of dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS) requires the precise identification of dengue virus (DV)-permissive target cells. In a previous study using unfractionated human peripheral blood mononuclear cells, we found that monocytes, but not B or T cells, were the principal DV-permissive cells in the absence of DV-immune pooled human sera (PHS) and the major mediators of antibody-dependent enhancement in the presence of PHS. To further identify DV-permissive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 40 publications
1
96
0
2
Order By: Relevance
“…54 To assess viral replication kinetics in a cell model that more closely reflects replication in vivo, we also monitored the replication of the two lineages daily over 2 days in primary human mo-DCs, which are considered primary targets for DENV infection in humans. [55][56][57] Because two different donors contributed mo-DCs, we initially tested for an effect of donor on viral replication, but we detected neither an interaction between donor and lineage (rmANOVA, df = 1, 18; P = 0.69) nor an overall effect of donor (rmANOVA, df = 1, 18; P = 0.98) on viral replication kinetics at 48 hours post-infection ( Figure 3A and B). We, therefore, combined data from both donors.…”
Section: Resultsmentioning
confidence: 99%
“…54 To assess viral replication kinetics in a cell model that more closely reflects replication in vivo, we also monitored the replication of the two lineages daily over 2 days in primary human mo-DCs, which are considered primary targets for DENV infection in humans. [55][56][57] Because two different donors contributed mo-DCs, we initially tested for an effect of donor on viral replication, but we detected neither an interaction between donor and lineage (rmANOVA, df = 1, 18; P = 0.69) nor an overall effect of donor (rmANOVA, df = 1, 18; P = 0.98) on viral replication kinetics at 48 hours post-infection ( Figure 3A and B). We, therefore, combined data from both donors.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the percentage of mononuclear cells that are macrophages is much lower than lymphocytes in spleen and LNs. 16 Hence, the contribution to the total binding sites for the radiotracer, that is, CD4 receptors per unit mass/volume of tissue, brought by the macrophages/ monocytes compartment is expected to be much lower than the contribution brought by the CD4 1 T cells. This is corroborated by the IHC conducted on CD3 1 cells which shows evidence of a substantial pool of T cells that survive the TBI in the spleen but not in the LNs, consistent with the imaging data presented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This fact has also been reported in previous studies, which have demonstrated that T and B cells are the target cells in dengue infection [23][24][25][26] . Another hypothesis suggests that monocytes are the primary targets in DENV infection and that T and B cells are not infected 27,28 . However, we did not observe this in our study, and in the contrary found that the smallest subpopulation .…”
Section: Discussionmentioning
confidence: 99%